2012
DOI: 10.1186/1744-8603-8-8
|View full text |Cite
|
Sign up to set email alerts
|

Global health funding and economic development

Abstract: The impact of increased national wealth, as measured by Gross Domestic Product (GDP), on public health is widely understood, however an equally important but less well-acclaimed relationship exists between improvements in health and the growth of an economy. Communicable diseases such as HIV, TB, Malaria and the Neglected Tropical Diseases (NTDs) are impacting many of the world's poorest and most vulnerable populations, and depressing economic development. Sickness and disease has decreased the size and capabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 11 publications
0
18
0
1
Order By: Relevance
“…Specifically, reduced health care spending may reduce GDP per capita, as (1) less healthy populations are less productive economically, and (2) reduced investments in health care and weaker efforts toward preventive measures can result in worsened outcomes, development of more severe disease, and requirements for more expensive care. 27 Therefore, reductions in GHS may culminate in greater costs to a nation's economy. 28 Our analysis has also shown that cuts in GHS adversely affect child health to a greater scale in low-income countries.…”
Section: Figurementioning
confidence: 99%
“…Specifically, reduced health care spending may reduce GDP per capita, as (1) less healthy populations are less productive economically, and (2) reduced investments in health care and weaker efforts toward preventive measures can result in worsened outcomes, development of more severe disease, and requirements for more expensive care. 27 Therefore, reductions in GHS may culminate in greater costs to a nation's economy. 28 Our analysis has also shown that cuts in GHS adversely affect child health to a greater scale in low-income countries.…”
Section: Figurementioning
confidence: 99%
“…Many deaths are associated with neglected diseases each year, but research to find a cure is still not a priority. Even though these diseases account for 90% of the global disease burden only 10% of global investment in health research is put towards developing cures (3). Every year ten million children die in low-income countries due to the contraction of neglected diseases (3).…”
Section: Discussionmentioning
confidence: 99%
“…1 This linkage in disproportionate increase in developmental delays and intellectual disabilities was once termed as new morbidity and was one of the impetuses for the emergence of the special needs movement in the US. 2 Many of these children are showing declines in cognitive functioning, delays in language skills, as well as poor motor and social skills.…”
Section: Introductionmentioning
confidence: 99%